THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON DATING BEHAVIOR WITH PARENT–CHILD RELATIONSHIPS AS A MEDIATING VARIABLE - Lubis, Suaidah; Situmeang, Sintong Ekapriasi; Nurhandayani, Ika; Manurung, Irma; Ningsih, Dwi Ayu; Hafnizar, Hafnizar; Syam, Tengku Nuranasyah; Simbolon, Lenny Marlina; Manurung, Dohar Mauli (Journal Analytica Islamica, 2026)
This study aimed to examine the effect of emotional intelligence on adolescents’ dating behavior, with the parent–child relationship as a mediating variable. Adolescent dating behavior is influenced by emotional regulation abilities and the quality of relationships with parents. This research employed a quantitative approach using an explanatory survey design and mediation analysis. The participants consisted of 209 twelfth-grade students from SMK Imelda Medan. Data were collected using emotional intelligence, parent–child relationship, and dating behavior scales developed in a 4-point Likert format. The results of validity testing indicated that all items were valid, while reliability analysis showed Cronbach’s Alpha coefficients exceeding 0.70, indicating good reliability. The findings revealed that emotional intelligence had a significant direct effect on adolescents’ dating behavior. Furthermore, emotional intelligence also demonstrated a significant indirect effect on dating behavior through the parent–child relationship, confirming its mediating role. These results suggest that higher emotional intelligence, supported by positive parent–child relationships characterized by emotional closeness, open communication, and a sense of security, contributes to healthier and more adaptive dating behavior among adolescents. This study contributes to the field of adolescent developmental psychology by providing empirical evidence on the psychological mechanisms linking emotional intelligence and dating behavior, particularly in the context of vocational secondary education. The findings also have practical implications for schools, parents, and psychology practitioners in developing intervention programs that focus on strengthening emotional intelligence and enhancing the quality of parent–child relationships to promote healthy adolescent dating behavior aligned with prevailing social values.